The role of agricultural extension television programs in disseminating information related to the control of whitefly insect on citrus trees And the extent to which citrus orchard owners benefit from this information. (Journal of the College of Basic Education, 2023)
The research aimed to stand on the role played by the indicative television programmes.Agricultural studies in the dissemination of information related to white fly insect control on treescitrus by determining the level of benefit of citrus orchard owners from theseinformation, and the content analysis method was used to analyze the content of the paragraphs presented byThrough these programs about this insect to get acquainted with the topics and methods that have been presentedIn addition, the method of collecting information was used in the field, and the district of Al-Khalis was chosen as a place.to be conducted and by using the personal questionnaire as a means of collecting data to identify the opinions of the owners ofCitrus orchards in the topics presented on this insect through these programsand the extent to which they benefited from it, and the topics on which they did not obtain sufficient information, and the methodstheir preferred submission for submission. The research also aimed to determine the relationship between the level ofRespondents from these programs with respect to whitefly and each of the independent factors:(age, educational level, agricultural experience).The results of the content analysis showed that the number of paragraphs presented through these programsinformation about this insect is not commensurate with the severity of infection with it, as it was shown that the balancing process inEmphasis on topics related to this insect were not taken into account when choosingThe topics presented, and other important topics related to this insect were not addressed.The style of speech is dominant in presenting the paragraphs of these programs, while the use of methods is less.other.As for the results of the field study, it showed that the percentage of follow-up and benefit from thisprograms by the owners of citrus orchards were high, but the extent of follow-up and benefitIt was to a small extent, and most of them attributed this to several reasons, including their lack of knowledge of the exact time.